Prenatal benzoate treatment in urea cycle defects. Issue 3 (10th November 2008) - Das, A M; Illsinger, S; Hartmann, H; Oehler, K; Bohnhorst, B; Kühn-Velten, W N; Lücke, T
Abstract : Objective: In patients with severe urea cycle defects (UCD) metabolic decompensation with hyperammonaemia typically occurs during the first days of life resulting in severe neurological damage or death. Benzoate can eliminate nitrogen independent of the urea cycle. Usually, benzoate is started soon after birth, but prenatal administration might improve metabolic stability. Design: Two fetuses with a prenatal diagnosis of UCD (female: citrullinaemia; male: ornithine transcarbamylase deficiency) were loaded with benzoate prenatally via the placenta by infusing their mothers with benzoate. Benzoate concentrations were measured in umbilical cord blood and the blood of the mothers and their newborns. Results: Therapeutic concentrations of benzoate were found in umbilical cord blood and in the children's blood. Thus, benzoate transfer across the placenta was demonstrated. Plasma ammonia and glutamine levels in the postnatal period were within the normal range. Conclusions: Benzoate infusion of the mother shortly before birth is safe and results in therapeutic levels of benzoate in umbilical cord blood.